MATHEMATICAL APPROACH OF DIFFUSION IN THE ELECTROCHEMICAL CONTEXT - Barrozo, Sidineia [UNESP]; Benedetti, Assis Vicente [UNESP] (Soc Brasileira Quimica, 2016)
The aim of this study was to explain in detail the mathematical methods used to deal with diffusion equations, mainly for students and researchers interested in electrochemistry and related areas. Emphasis was placed on the deduction and resolution of diffusion equations, as well as addressing cartesian, spherical and cylindrical coordinates. Different aspects of mass transfer processes were discussed including the importance of the resolution of Fick's laws equations to understand and derive parameters of the electroactive species (e.g., diffusion coefficients, formal electrode potentials) from the electrochemical techniques. As an example, the resolution of diffusion equations for a reversible reduction process of soluble oxidized species was presented for the chronopotentiometry technique. This study is envisaged to broaden the understanding of these frequently used methods, in which mathematical deductions are not always completely understood.
Keywords: diffusion; mass transfer; diffusion equations; mathematical resolution; electrochemical